2007
DOI: 10.1177/0363546507300693
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Sports in Cartilage Regeneration after Autologous Chondrocyte Implantation

Abstract: Physical training improves long-term results after autologous chondrocyte implantation of the knee and should be carried out for at least 2 years after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(60 citation statements)
references
References 51 publications
(50 reference statements)
2
58
0
Order By: Relevance
“…119 Postoperative participation in sports improved the long-term functional results after ACI. 32,86,180 The timing of return to sports varies from 7 to 18 months, depending on the surgical technique. Average time to return to sport was longest for ACI (18-25 months) and shortest for OATS (6.5-7 months).…”
Section: Return To Sport After Knee Articular Cartilage Repairmentioning
confidence: 99%
“…119 Postoperative participation in sports improved the long-term functional results after ACI. 32,86,180 The timing of return to sports varies from 7 to 18 months, depending on the surgical technique. Average time to return to sport was longest for ACI (18-25 months) and shortest for OATS (6.5-7 months).…”
Section: Return To Sport After Knee Articular Cartilage Repairmentioning
confidence: 99%
“…41 The creation of stable vertical walls allows for easy placement of a synthetic patch over the lesion site (an off-label use of the Bio-Gide [Geistlich Biomaterials, Wolhusen, Switzerland], which has not been approved by the US Food and Drug Administration for cartilage repair, though many like it are on the market and used with indication for tendon reconstruction). 34 The patch is then carefully sewn into place and sealed using fibrin glue (FIGURE 4). A small opening toward the top of the patch is utilized to inject the cultured chondrocytes.…”
Section: Restorative Technique: Autologous Chondrocyte Implantationmentioning
confidence: 99%
“…Note that it was not only the selection of study time points that varied but also the range in data-collection times about those points, which in some instances was up to 5 years. 41,44 However, the majority of the studies did not report these range values. These inconsistences in reporting are pertinent to rehabilitation, as it is a time-based process.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the studies reported multiple assessments with a mean follow-up of 38.6 months. Four studies 33,34,37,39,41 reported mean followup periods of 5 years, 1 study 30 reported 7.5 years, and another study, 28 10 years. However, the majority of the studies only reported mean assessment time and did not report the minimum and maximum assessment time.…”
Section: Data Synthesismentioning
confidence: 99%
See 1 more Smart Citation